Effect of The Drying Time of Unhulled Rice on The Rice Quality of Variety Inpari-7 - I. Ismail; Muhammad Akhsan Akib; Murni Mahmud (Universitas Sembilanbelas November Kolaka, 2022)
High rice consumption necessitates an improvement in rice quality. Rice quality issues can result from pest attacks, unhulled rice transportation, harvesting, and drying. An alternative is to use a drier to enhance the quality of rice. Therefore, research to evaluate the quality of rice dried in a dryer with various drying times is required. The Rice Milling Unit, Harapan Village Unit Cooperative (VUC), Tiroang Sub-District, Pinrang District, located at coordinates 3O48'41